2021
DOI: 10.1002/anie.202110589
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming Inactive Lithium with a Triiodide/Iodide Redox Couple for Practical Lithium Metal Batteries

Abstract: High-energy-density lithium (Li)m etal batteries suffer from as hort lifespan owing to apparently ceaseless inactive Li accumulation, which is accompanied by the consumption of electrolyte and active Li reservoir,s eriously deteriorating the cyclability of batteries.H erein, at riiodide/ iodide (I 3 À /I À )redox couple initiated by stannic iodide (SnI 4 )is demonstrated to reclaim inactive Li. The reduction of I 3 À converts inactive Li into soluble LiI, which then diffuses to the cathode side.T he oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 71 publications
(11 reference statements)
2
36
0
Order By: Relevance
“…[25b] In addition, the amount of I 2 should be strictly controlled to prevent the further pitting corrosion on active Li according to the previous literature. [23,26] To explore the effect of additives on solvation structure, nuclear magnetic resonance (NMR) was employed. A series of LPFN-i 2 type electrolytes with 5 vt% varied G4 n were prepared (denoted as G n m 4 , n,m represents the concentration of LiNO 3 in G4 and in bulk electrolyte respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[25b] In addition, the amount of I 2 should be strictly controlled to prevent the further pitting corrosion on active Li according to the previous literature. [23,26] To explore the effect of additives on solvation structure, nuclear magnetic resonance (NMR) was employed. A series of LPFN-i 2 type electrolytes with 5 vt% varied G4 n were prepared (denoted as G n m 4 , n,m represents the concentration of LiNO 3 in G4 and in bulk electrolyte respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] In the previous work, we have demonstrated that the LiI formation is based on a spontaneous reaction between iodine (I 2 ) species and Li metal, which enables the elimination of dead Li and SEI delicately driven by slight cell energy. [ 34,35 ] As such, it is highly desired that I 2 species be beneficial to the formation of a stable interphase between PEO electrolyte and Li metal. In this work, we propose a PEO‐LiTFSI‐I 2 electrolyte for stable solid‐state LMBs (SSLMBs).…”
Section: Introductionmentioning
confidence: 99%
“…However, irreversible reactions inevitably occur between highly reactive anodes and electrolytes, which severely plagues the life span of batteries (8)(9)(10). Despite the formation of solid electrolyte interphase (SEI), yet the irreversible reactions occur continuously because of the fragility of SEI (11)(12)(13). Therefore, inhibiting the reactions occurring at anode/ electrolyte interface is necessary for long-cycling rechargeable batteries (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%